2020
DOI: 10.1177/1460458220936395
|View full text |Cite
|
Sign up to set email alerts
|

On the medication distribution system for home health care through convenience stores, lockers, and home delivery

Abstract: Medication distribution service can be delivered based on a combination of home delivery and customer pickup. That is, medications are delivered either to customers’ homes directly or to the pickup facilities (e.g. lockers) close to customers’ homes. In Taiwan, there are more than 11,000 convenience stores that provide a 24-h service for customers to pick up the ordered items from e-commerce, which is unique to the world. In the medication distribution system, convenience stores can provide a unique opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This special issue features one article reporting on work developing medication distribution system to support existing home medication services that link convenience stores, lockers and home delivery in Taiwan. 14 The proposed system allows simultaneous determination of convenience store chains, pickup locations of convenience stores and lockers, vehicle routes for convenience stores and lockers, and vehicle routes for customers' homes. Initial simulation has showed that the system can potentially fit individual needs for customers, minimize operation costs and improve the efficiency of medication home delivery.…”
Section: Contributionsmentioning
confidence: 99%
“…This special issue features one article reporting on work developing medication distribution system to support existing home medication services that link convenience stores, lockers and home delivery in Taiwan. 14 The proposed system allows simultaneous determination of convenience store chains, pickup locations of convenience stores and lockers, vehicle routes for convenience stores and lockers, and vehicle routes for customers' homes. Initial simulation has showed that the system can potentially fit individual needs for customers, minimize operation costs and improve the efficiency of medication home delivery.…”
Section: Contributionsmentioning
confidence: 99%
“…However, there is newfound impetus to leverage on this service considering its unique contactless nature which is critical during the pandemic season. 3 Similar locker service models have also been successfully implemented in countries such as Malaysia, 4 Netherlands 5 and Taiwan 6 in response to COVID-19.…”
Section: Introductionmentioning
confidence: 99%